Pretreatment and Multi-Feed Anaerobic Co-digestion of Agro-Industrial Residual Biomass for Improved Biomethanation and Kinetic Analysis - Prajapati, Kishan Kumar; Pareek, Nidhi; Vivekanand, Vivekanand (Frontiers in Energy Research, 2018)
Batch biochemical methane potential (BMP) test of agro-industrial, agricultural, and municipal solid waste (MSW) individuals like groundnut straw, rice bran, and guar husk, mung bean husk (MBH), wheat straw (WS) and organic fraction of municipal solid waste (OFMSW), under mesophilic conditions, were performed to evaluate the biogas potential. BMP test for multi-feed anaerobic co-digestion (AcoD) of WS, OFMSW, and MBH at five mixing ratio was performed to evaluate the synergistic effect of multi feed-stocks of blending the feedstocks. Mixture ratio having OFMSW:WS:MBH of 25:5:70% composition resulted into 37, 20, and 4% higher methane yield up to 280 ml/g Volatile solid (VS) in comparison with mono-digestion of OFMSW, WS and MBH. Ultrasonic pretreatment was also performed and the experimental results showed that varying the sonication time have a significant improvement on substrate’s biodegradation and solubilization augmenting the methane yield from OFMSW, WS, and MBH by 71, 75, and 46% respectively at sonication period of 60 min. Effect of pretreatment on the substrate studied through Scanning electron microscopy (SEM), XRD and FT-IR analysis. Cone and Exponential models showed an average coefficient of determination R2=0.9855 and R2=0.9893 respectively, and RMSE values for cone model was lower than that of Exponential model showing Cone model was more precised.